「토지대장」을 통해 본 토지생산성의 변화(1910-1961) : 김제시 죽산면 사례연구 - 조석곤 (한국농촌경제연구원, 2013)
This paper analyzes trends of land productivity from the early 1910s to the late 1950s in Korea. The land productivity increased rapidly during the colonial era especially in the lands owned by Japanese landlords, mainly because they had purchased cheaper lands with low productivity. Although the land productivity in Japanese-owned lands increased rapidly, it did not exceed that of Korean-owned lands. This was because the land productivity in Korean-owned lands increased as well. Moreover, after the Korean Land Reform, the land productivity in the late 1950s recovered or exceeded that of the late 1930s, even after the chaotic years of the Korean War. The implications of the results are as follows: first, while land productivity increased under the colonial landlord system, Korean landlords had also contributed to the increase as much as Japanese landlords. Secondly, the fact that the land productivity under the owner-peasant system was as good as the colonial landlord system shows that the agricultural skills embedded in petty peasants were important as good as the role of colonial landlords was.
Keywords: 식민지기 토지생산성; 농지개혁; 식민지지주제; 자작농체제; land productivity in colonial Korea; Land Reform; colonial landlord system; owner-peasant system